Mechano‐sensing and transduction by endothelial surface glycocalyx: composition, structure, and function. (7th February 2013) - Fu, Bingmei M.; Tarbell, John M.
Abstract: The endothelial cells (ECs) lining every blood vessel wall are constantly exposed to the mechanical forces generated by blood flow. The EC responses to these hemodynamic forces play a critical role in the homeostasis of the circulatory system. To ensure proper EC mechano‐sensing and transduction, there are a variety of mechano‐sensors and transducers that have been identified on the EC surface, intra‐ and trans‐EC membrane and within the EC cytoskeleton. Among them, the most recent candidate is the endothelial surface glycocalyx (ESG), which is a matrix‐like thin layer covering the luminal surface of the EC. It consists of various proteoglycans, glycosaminoglycans, and plasma proteins, and is close to other prominent EC mechano‐sensors and transducers. The ESG thickness was found to be in the order of 0.1–1 µm by different visualization techniques and in different types of vessels. Detailed analysis on the electron microscopy (EM) images of the microvascular ESG revealed a quasi‐periodic substructure with the ESG fiber diameter of 10–12 and 20 nm spacing between adjacent fibers. Atomic force microscopy and optical tweezers were applied to investigate the mechanical properties of the ESG on the cultured EC monolayers and in solutions. Enzymatic degradation of specific ESG glycosaminoglycan components was used to directly elucidate the role of the ESG in EC mechano‐sensing and transduction by measuring the shear‐induced productions of nitric oxide and prostacyclin, two characteristic responses of the ECs to the flow. The unique location, composition, and structure of the ESG determine its role in EC mechano‐sensing and transduction. WIREs Syst Biol Med 2013, 5:381–390. doi: 10.1002/wsbm.1211 This article is categorized under: Models of Systems Properties and Processes > Cellular Models Biological Mechanisms > Cell Signaling Physiology > Organismal Responses to Environment